Improved Co‐Firing of Ferrite and Dielectric Tape Based on Master Sintering Curve Predictions and Shrinkage Mismatch Calculations. Issue 3 (1st March 2013) - Brandt, Björn; Naghib‐zadeh, Hamid; Rabe, Torsten; Blendell, J.
<x xml:space="preserve">Abstract</x> Co‐firing of low temperature co‐fired ceramics (LTCC) and functional ceramics like ferrites is a promising approach to increase the level of integration in future microsystems, and to create new applications for LTCC technology. Besides the development of compatible material combinations, the configuration of the sintering process is an important issue for successful co‐firing. A method is presented to derive the linear shrinkage mismatch of a material combination based on density data calculated from the master sintering curves (MSCs) of the individual materials. The influence of the firing profile on the constraint in the combined multilayer can be anticipated using this method. To investigate and improve the co‐firing of ferrite and dielectric tape, the shrinkage mismatch with respect to heating rate was studied. A significant reduction of shrinkage mismatch was found for increased heating rates. The calculated results are verified by lateral shrinkage measurements on combined laminates.